Identifikasi Bahaya dan Resiko K3 Menggunakan Metode HIRARC di PT LPN Shipyard - Nurul Arafah; Haniarti, Haniarti; Amir, Rahmi (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
Occupational Health and Safety (OHS) is an important aspect in the ship repair industry because work activities in shipyards have a high potential for hazards, such as welding, painting, working in confined spaces, working at heights, and the use of hazardous chemicals. This study aims to identify hazards, assess risk levels, and provide control recommendations using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method at PT LPN Shipyard. The research method used is quantitative descriptive with data collection through field observations, interviews, and company document reviews. Risk assessment is performed using a Likelihood × Severity matrix to classify risk levels into low, medium, high, and extreme. The research results show that among all the main activities at PT LPN Shipyard, several potential hazards were found with risk distribution: moderate risk (50%), high risk (40%), and extreme risk (10%). The highest risks are found in painting works in confined spaces, exposure to welding fumes, the use of flammable chemicals, and work at heights. The main contributing factor to these risks is unsafe actions by workers, such as not using personal protective equipment (PPE), using mobile phones while working, and non-ergonomic manual handling.The existing controls are still limited to administrative aspects and the use of PPE. Therefore, it is recommended to implement additional controls such as technical engineering (mechanical ventilation, gas detectors, local exhaust ventilation), strict supervision of the Permit To Work, and regular safety training to enhance worker awareness.